2020
DOI: 10.3389/fimmu.2020.00302
|View full text |Cite
|
Sign up to set email alerts
|

Gender Disparity Impacts on Thymus Aging and LHRH Receptor Antagonist-Induced Thymic Reconstitution Following Chemotherapeutic Damage

Abstract: One of the main consequences of thymus aging is the decrease in naïve T cell output. This condition accelerates at the onset of puberty, and presents as a major clinical complication for cancer patients who require cytoablative therapy. Specifically, the extensive use of chemotherapeutics, such as cyclophosphamide, in such treatments damage thymic structure and eliminate the existing naïve T cell repertoire. The resulting immunodeficiency can lead to increased incidence of opportunistic infections, tumor growt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 54 publications
1
20
0
Order By: Relevance
“…Puberty is the result of activation of the hypothalamopituitary-gonadal axis and, as a consequence, of the increased production of androgens and estrogens usually starting between the age of 8 and 13 years in girls and 9 and 14 years in boys (9). Onset of puberty is associated with a decline in thymic function, and possibly splenic function as well (10,11). Yet, the exact differences that age and puberty have on the development of immune reconstitution post-HSCT, GvHD, and the induction of immune tolerance are still incompletely studied.…”
Section: Introductionmentioning
confidence: 99%
“…Puberty is the result of activation of the hypothalamopituitary-gonadal axis and, as a consequence, of the increased production of androgens and estrogens usually starting between the age of 8 and 13 years in girls and 9 and 14 years in boys (9). Onset of puberty is associated with a decline in thymic function, and possibly splenic function as well (10,11). Yet, the exact differences that age and puberty have on the development of immune reconstitution post-HSCT, GvHD, and the induction of immune tolerance are still incompletely studied.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to the clear increase in the number of thymocytes after cytoablative treatment followed by SSI, the TEC compartment of the thymus appears to increase in cell size, but not necessarily due to TEC proliferation (85,92). Elegant immunofluorescence analyses of TECs demonstrated that morphological changes in TECs, and not de novo regeneration, were largely responsible for the expansion of the cortical region of the aged thymus after SSI treatment (92).…”
Section: Strategies For Enhancing Thymic Regenerationmentioning
confidence: 91%
“…Accordingly, the most remarkable effect on thymus size and output was uncovered as a consequence of physical ( 84 ) or chemical castration in both sexes ( 51 , 85 ), revealing the potential for reversal of age-related thymic atrophy. These effects may be blocked by administration of sex hormones, demonstrating the direct effect of androgens on immunity, and specifically, on thymus involution.…”
Section: Strategies For Enhancing Thymic Regenerationmentioning
confidence: 99%
See 1 more Smart Citation
“…With aging, a thymic atrophy results in a decrease of functional naïve CD4+ and CD8 T cells [ 95 ]. This decline is more pronounced in males than in females [ 96 ] and is more noticeable for CD8 T cells with a peripheral oligo-clonal expansion of memory T cells, which in general provides a contracted T cell antigen receptor (TCR)-repertoire diversity inducing immunosenescence. In addition, aging causes CD4+ T cells to become longer-lived but functionally impaired with reduced proliferation and IL-2 production.…”
Section: Senescence In the Immune Response To Fight Cancermentioning
confidence: 99%